Analisa Value for Money Pada Kinerja Keuangan Kota Bogor 2020 – 2022 - Achmad Mufaqih; Sonny Fransisco; Raditya Ayu; Aulia Apriliana (Jurnal Mutiara Ilmu Akuntansi, 2024)
Based on the explanation of the findings above, it can be concluded that: Bogor City's financial performance is measured by economic indicators from 2020 to 2022, reaching an average of 68.5%, this figure is included in the economic category because the level of independence ratio is below 100%. Bogor City's financial performance as measured by the level of efficiency ratio in 2020 to 2022 shows an average efficiency level of 101% and the higher the efficiency level, it falls into the non-efficiency category, because it is more than 100%. Bogor City's financial performance is measured by the effectiveness ratio in 2020 to 2022 from the overall average which reached an effective ratio of 110.3% and is included in the effective category because the effective ratio is above 100%.